Inhibition of human gall bladder mucus synthesis in patients undergoing cholecystectomy. Issue 8 (August 1992) - Rhodes, M; Allen, A; Dowling, R H; Murphy, G; Lennard, T W
Abstract : Hypersection of gall bladder mucus is associated with gall stone formation in animal models. Aspirin inhibits both mucus synthesis and secretion, prevents gall stone formation in animals and reduces gall stone recurrence in man after dissolution therapy. Mucus biosynthesis in human gall bladder mucosal explants is inhibited by aspirin in vitro. We have studied the effects of aspirin in vivo. Fifty five patients with functioning gall bladder and stones have been randomised, 27 to group 1 (aspirin EC 300 mg once daily for seven days before cholecystectomy) and 28 to group 2 (controls). Gall bladder bile composition was analysed and mucus synthesis rates measured using 3H-glucosamine incorporation into mucosal explants cultured for 24 hours. Patient age, sex, and gall bladder histology were similar in both groups. There were no differences in stone composition, gall bladder bile calcium concentration, cholesterol saturation and cholesterol nucleation time. The mean 3H-glucosamine incorporation in aspirin treated patients was 1347 fmol/g wet weight as compared with 2008 fmol/g wet weight in controls (95% confidence interval 222-1100, p<0.005, unpaired t test). This reduction in biosynthesis was associated with gall bladder bile mucus concentrations of 7.6 mg/ml in patients and 7.1 mg/ml in controls (ns). Treatment with aspirin led to a significant reduction in mucus biosynthesis by the gall bladder mucosa. This action is consistent with a role for aspirin in the prevention of gall stones.